2022
DOI: 10.3389/fnint.2022.920271
|View full text |Cite
|
Sign up to set email alerts
|

Research in Mindfulness Interventions for Patients With Fibromyalgia: A Critical Review

Abstract: Fibromyalgia is one of the most common causes of widespread chronic pain. It has a huge impact on the quality of life, namely because it appears earlier in life than most of the chronic pain conditions. Furthermore, emotional-cognitive distress factors, such as depression and anxiety, are a common feature in patients with fibromyalgia. The neurobiological mechanisms underlying fibromyalgia remain mostly unknown. Among non-pharmacological treatments, cognitive-behavioral therapy has been used during the last de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 59 publications
0
6
0
2
Order By: Relevance
“…10 Adapted mindfulness approaches for chronic pain are in the early stages and high drop‐out rates remain an issue. 22 We therefore consider that our work remains topical and relevant today.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Adapted mindfulness approaches for chronic pain are in the early stages and high drop‐out rates remain an issue. 22 We therefore consider that our work remains topical and relevant today.…”
Section: Discussionmentioning
confidence: 99%
“…However, research on mindfulness for people with chronic pain remains inconclusive and further research is recommended in the current NICE guidelines 10 . Adapted mindfulness approaches for chronic pain are in the early stages and high drop‐out rates remain an issue 22 . We therefore consider that our work remains topical and relevant today.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of research suggests that mindfulness may improve neuropsychiatric symptoms that commonly occur in a range of neurological disorders [11]. Specifically, there is evidence for the effectiveness of mindfulness-based interventions in patients with movement disorders associated with behavioural symptoms, such as Parkinson disease [12], multiple sclerosis [13][14][15][16], epilepsy [17,18], sleep disorders [19][20][21][22], headache [23][24][25][26], and chronic pain symptoms [27][28][29]. Patients with acquired brain pathologies such as mild traumatic brain injury [30,31], cerebrovascular accidents [32,33] and dementia [34][35][36] have also been shown to potentially benefit from mindfulness-based interventions, as well as their carers [37][38][39].…”
Section: The Third Wave Of Cognitive Behavioural Therapy For Neuropsy...mentioning
confidence: 99%
“…Mind-body interventions: Mind-body interventions, such as mindfulness-based stress reduction (MBSR), have demonstrated efficacy in improving symptoms of fibromyalgia by targeting stress, anxiety, and depression [ 45 ]. A recent study published in 2022 investigated the effectiveness of MBSR in fibromyalgia patients and reported positive outcomes, including reductions in pain and fatigue, as well as improvements in quality of life [ 46 ]. Similarly, a study published in 2012 examined the effectiveness of CBT in fibromyalgia patients and found that it effectively reduced pain, anxiety, and depression, while enhancing physical function [ 47 ].…”
Section: Reviewmentioning
confidence: 99%